Lecturers' attitude toward and anxiety in writing English academic papers for international publications - Hartono Hartono; Ruseno Arjanggi (University of Kuningan, 2020)
This study was aimed at investigating attitude and anxiety of Indonesian lecturers in writing English papers for international publications, together with the influence of gender and functional grades on them. It involved lecturers of a private university in Semarang, Central Java, Indonesia (n=62) who were attending a training on English academic writing especially designed to help them prepare manuscripts for international publications. Data were collected by questionnaires and analyzed using t-test and ANOVA. The study found that the attitude toward writing was positive. Three aspects of attitude namely behavioral, cognitive, and affective were all positive. The anxiety in writing English papers was found to be moderate and somatic anxiety was the type of anxiety the lecturers suffered the most. There was no difference on the attitude and level of anxiety across gender but there was a difference on the level of anxiety across functional grades. As attitude and anxiety predict the success of writing efforts, which may then affect the success of publication, the issue of attitude and anxiety needs to be addressed in the effort of increasing the productivity of Indonesian lecturers in making international publications.